Computed Tomography (CT): Advances In CT Techniques, Such As Dual-Energy Computed Tomography (DECT) Or Low-Dose CT, Can Be Studied (Journal of Namibian Studies : History Politics Culture, 2022)
Computed tomography (CT) continues to evolve, with significant advancements in recent years. This research explores two critical techniques: dual-energy CT (DECT) and low-dose CT.• Dual-Energy Computed Tomography (DECT):- DECT utilizes two distinct X-ray energy levels for material differentiation.- Applications include virtual monoenergetic images, material decomposition, and iodine concentration maps. - Recent research findings demonstrate its value in various clinical scenarios.• Low-Dose CT:- LDCT reduces radiation exposure while maintaining diagnostic quality.- Crucial for lung cancer screening, LDCT detects early-stage nodules.- The National Lung Screening Trial (NLST) supports its efficacy in reducing lung cancer-related deaths.